Dual-species cultivation of microalgae and yeast for enhanced biomass and microbial lipid production - Liu, Lu; Chen, Junhui; Lim, Phaik Eem; Wei, Dong (Springer Verlag, 2018)
Oleaginous microalgae and yeasts are well known as potential feedstocks for biofuels and other fatty acid-derived materials. Microalgae-yeast mixed culture has gained more attention recently for the improvement of microbial lipid production economically. In the present work, combinations of two Chlorella species with oleaginous yeast at different ratios by the mixed culture mode were evaluated for the improvement of biomass and lipid production. Yeast cells dominated in a dual-species cultivation system when co-cultivated with Chlorella vulgaris. Compared to the monoculture and other three studied consortia, the mixed culture of Chlorella pyrenoidosa and Rhodotorula glutinis with a ratio of 3:1 achieved maximum biomass concentration and lipid productivity. Further optimization of the C/N ratio in the medium was carried out using this consortium. At a C/N ratio of 64, biomass concentration and lipid yield reached 6.12 ± 0.31 and 2.48 ± 0.09 g L −1 , respectively. The highest total fatty acid (TFA) productivity (175.64 ± 2.32 mg L −1 day −1 ) obtained in the mixed culture was twofold than that in the monoculture. Additionally, dissolved oxygen and pH were found to be adjusted synergistically in the mixed culture. These results demonstrated that an artificial consortium of microalgae and yeast is a promising approach for future applications in microbial lipid production.